Reduction of Phase-Modulation to Intensity-Modulation Conversion Noise Effect Using Delayed Self-Homodyne Optical Orthogonal Frequency Division Multiplexing System - Younus Nidham Ali Mandalawi; Syamsuri Yaakob; Wan Azizun Wan Adnan; Raja Syamsul Azmir Raja Abdullah; Mohd Hanif Yaacob; Zuraidah Zan (IEEE Photonics Journal, 2021)
Self-homodyne optical orthogonal frequency division multiplexing (OFDM) transmission system is a variant of self-coherent systems with a relaxed laser linewidth requirement as opposed to a full coherent system. The system is designed by transmitting a carrier together with the subcarriers, ensuring a strong phase-correlation between them at a receiver compared to the coherent system where only the subcarriers are transmitted. Despite the strong phase-correlation, the laser phase noise (PN) can still degrade the self-homodyne system performance due to the interaction of the PN with a chromatic dispersion (CD) induces a phase-modulation to intensity-modulation (PM-to-IM) conversion noise which cannot be canceled using a balanced-receiver. This imposes a high noise pedestal underneath each subcarrier, with the highest pedestal's peak imposed beneath the subcarriers that are farthest away from the carrier. This in turn produces a phase-decorrelation between the carrier and subcarriers which degrades the Q-factor between the lowest and highest subcarrier frequencies. In this work, the effect of the PM-to-IM conversion noise is reduced for the transmission of up to 174 Gb/s using a simple delay-line assigned to realign the phase-decorrelation of the subcarriers. With this technique, the subcarriers Q-degradation can be improved and the total transmission length can be tripled with Q-improvements of 5.4, 5.3, and 5-dB for 16-quadrature amplitude modulation (QAM) over 1360 km, 32- QAM over 800 km, and 64-QAM over 480 km, respectively, using 10-MHz LW with a 15-GHz total signal bandwidth. For 29 GHz signal bandwidth, the phase-walk-off of the high frequency subcarrier becomes more severe where the introduced delay can increase the transmission length by 2.5 times than without the delay, which increased the signal tolerance to the conversion noise.